Genome-wide profiling of diel and circadian gene expression in the malaria vector Anopheles gambiae - Rund, Samuel S.C; Hou, Tim Y; Ward, Sarah M; Collins, Frank H; Duffield, Giles E (Proceedings of the National Academy of Sciences - PNAS, 2011)
Anopheles gambiae, the primary African vector of malaria parasites, exhibits numerous rhythmic behaviors including flight activity, swarming, mating, host seeking, egg laying, and sugar feeding. However, little work has been performed to elucidate the molecular basis for these daily rhythms. To study how gene expression is regulated globally by diel and circadian mechanisms, we have undertaken a DNA microarray analysis of An. gambiae under light/dark cycle (LD) and constant dark (DD) conditions. Adult mated, non-blood-fed female mosquitoes were collected every 4 h for 48 h, and samples were processed with DNA microarrays. Using a cosine wave-fitting algorithm, we identified 1,293 and 600 rhythmic genes with a period length of 20-28 h in the head and body, respectively, under LD conditions, representing 9.7 and 4.5% of the An. gambiae gene set. A majority of these genes was specific to heads or bodies. Examination of mosquitoes under DD conditions revealed that rhythmic programming of the transcriptome is dependent on an interaction between the endogenous clock and extrinsic regulation by the LD cycle. A subset of genes, including the canonical clock components, was expressed rhythmically under both environmental conditions. A majority of genes had peak expression clustered around the day/night transitions, anticipating dawn and dusk. Genes cover diverse biological processes such as transcription/translation, metabolism, detoxification, olfaction, vision, cuticle regulation, and immunity, and include rate-limiting steps in the pathways. This study highlights the fundamental roles that both the circadian clock and light play in the physiology of this important insect vector and suggests targets for intervention.